Algebra II (check)

posted by .

Assume that no denominator equals 0.

sqrt 16x^2y^4

= sqrt (4x)y^2
= 4xy^2(answer)

  • Algebra II (check) -

    Your answer is correct. Another possible answer is -4xy^2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how would you simplify this equation: y = (x+3)/[(4-sqrt(16+h))] please help me! you have three variables. I am not certain "simplify" is an appropriate term here. ohhhh it was my mistake. I meant: y = h/[(4-sqrt(16+h))] y = h/[(4-sqrt(16+h))] …
  2. Math

    How do you find a square root of a number that's not a perfect square?
  3. algebra,math,help

    Use Property 2 to simplify each of the following radical expressions. sqrt (10)/ sqrt(49) My answer: sqrt (10) / (7) THis next one i need help: Use the properties for radicals to simplify each of the following expressions. Assume that …
  4. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  5. algebra

    simplify by combining like terms: x sqrt(18) - 3 sqrt(8x)sqrd If <sqrt(8x)sqrd> means [sqrt(8x)]^2, then that also equals 8x. So x sqrt(18) - 3 sqrt(8x)sqrd = x[sqrt(9*2)-3*8] = 3x(sqrt 2 -3
  6. Algebra

    1 last square root : Rationalize the denominator 5/sqrt[3]+sqrt[5]= 5*sqrt[3]-sqrt[5]/ sqrt[3]sqrt5[5]*sqrt[3]-sqrt[5]= 5sqrt[3]-5sqrt[5]/sqrt[9]-sqrt[15]+sqrt[15]- sqrt[25]= 5sqrt[3]-5sqrt[5]/-16 = 5sqrt[3]-5sqrt[5]/ -2
  7. algebra

    Rationalize the denominator, assume that all expressions under radicals represent postive numbers. sqrt:a - sqrt:b/sqrt:a + sqrt:b
  8. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?
  9. 9th grade algebra (completing square)

    Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x
  10. algebra

    am I right? 1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt 56x^2 28x 2x sqrt 14*** 2x sqrt 7 sqrt 14x2 3. Simplify the radical expression. sqrt 490y^5w^6 2 sqrt 135y^2

More Similar Questions